Drones for research on sea turtles and other marine vertebrates – A review - Nicole Esteban (Biological Conservation, 2019)
We review how unmanned aerial vehicles (UAVs), often referred to as drones, are being deployed to study the abundance and behaviour of sea turtles, identifying some of the commonalities and differences with studies on other marine vertebrates, including marine mammals and fish. UAV studies of all three groups primarily focus on obtaining estimates of abundance, distribution and density, while some studies have provided novel insights on the body condition, movement and behaviour of individuals (including inter-specific interactions). We discuss the emerging possibilities of how UAVs can become part of the standard methodologies for sea turtle ecologists through combining information on abundance and behaviour. For instance, UAV surveys can reveal turtle densities and hence operational sex ratios of sea turtles, which could be linked to levels of multiple paternity. Furthermore, embedding UAV surveys within a mark-recapture framework will enable improved abundance estimates. The complexity of behaviours revealed by direct observations of sea turtles and animal-borne cameras can also be examined using UAV footage, complementing studies using electronic tags, such as time-depth recorders and satellite transmitters. Overall, UAVs provide a low-cost approach of quantifying the flexibility of marine animal behaviour, allowing us to integrate information on abundance to establish how individuals respond to the presence of other organisms and the immediate environment.